2006
DOI: 10.1124/jpet.106.110429
|View full text |Cite
|
Sign up to set email alerts
|

In 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine-Treated Primates, the Selective 5-Hydroxytryptamine 1a Agonist (R)-(+)-8-OHDPAT Inhibits Levodopa-Induced Dyskinesia but Only with\ Increased Motor Disability

Abstract: 5-Hydroxytryptamine 1a (5-HT 1a ) receptor agonists, such as sarizotan and tandospirone, are reported to reduce levodopainduced dyskinesia in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated macaques and in Parkinson's disease without worsening motor disability. However, these compounds are not specific for 5-HT 1a receptors and also possess dopamine antagonist actions. We now report on the effects of (2R), a selective 5-HT 1a agonist lacking dopaminergic activity, on motor disability and dyskinesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 47 publications
5
74
0
Order By: Relevance
“…Collectively, these findings show that the anti-dyskinetic actions of 5-HT 1A R agonists may be due, in part, to their impact on the corticostriatal glutamate system. The acute, chronic, and prophylactic anti-dyskinetic effects of 5-HT 1A R stimulation have been well-characterized in both preclinical (Bibbiani et al 2001;Iravani et al 2006;Carta et al 2007;Eskow et al 2007) and clinical investigations (Olanow et al 2004;Bara-Jiminez et al 2005;Goetz et al 2007). Unfortunately, a number of studies have also suggested that 5-HT 1A R agonists may worsen PD symptoms.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Collectively, these findings show that the anti-dyskinetic actions of 5-HT 1A R agonists may be due, in part, to their impact on the corticostriatal glutamate system. The acute, chronic, and prophylactic anti-dyskinetic effects of 5-HT 1A R stimulation have been well-characterized in both preclinical (Bibbiani et al 2001;Iravani et al 2006;Carta et al 2007;Eskow et al 2007) and clinical investigations (Olanow et al 2004;Bara-Jiminez et al 2005;Goetz et al 2007). Unfortunately, a number of studies have also suggested that 5-HT 1A R agonists may worsen PD symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, a number of studies have also suggested that 5-HT 1A R agonists may worsen PD symptoms. For example, Iravani et al (2006) found that the more potent ±8-OH-DPAT enantiomer, +8-OH-DPAT, reduced LID but worsened motor disability. Clinically, high doses of the 5-HT 1A R agonists tandospirone and sarizotan have been reported to exacerbate parkinsonian features (Kannari et al 2002;Goetz et al 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…8,9 Unfortunately, a number of studies have also shown that 5-HT 1A R agonists may, in some cases, worsen PD symptoms. For example, the more potent enantiomer +8-OH-DPAT reduced LID but worsened motor disability, 10 inducing a 5-HT-like syndrome. 11 Clinically, high doses of the 5-HT 1A R agonists tandospirone and sarizotan have been reported to exacerbate parkinsonian features.…”
mentioning
confidence: 99%
“…Many approaches to eliminating LID therefore tend to focus instead on manipulating factors that regulate serotonergic cell activity, such as serotonergic autoreceptors that participate in serotonergic homeostatic mechanisms. Simply decreasing serotonergic cell activity by administering serotonin autoreceptor agonists has the drawback of also reducing the amount of dopamine released into the extracellular space, tending to worsen PD symptoms (Iravani et al, 2006). Carta et al (2008) argue that it is reasonable to use 5-HT autoreceptor agonists especially because the DA intermixed with the 5-HT released by the serotonergic cell effectively lowers the binding of 5-HT to 5-HT autoreceptors and induces the cells to be over-active.…”
Section: Possible Mechanisms Of Serotonergic Involvement In Pd Motor mentioning
confidence: 99%